PMPD's Foreign Policy Vision in the Evolving Global Dynamics - Lamichhane, Dron Prasad (State, Society and Development: PMPD Perspectives, 2025)
This article assesses Nepal's Foreign Policy 2020 in light of Madan Bhandari's foreign policy vision as articulated in People's Multiparty Democracy (PMPD), which emphasizes nationalism, non-alignment, sovereignty, and people-centric development. Foreign Policy 2020 is the first official document of its kind published after the promulgation of Nepal’s new constitution in 2015. It reflects the aspirations of the Nepali people and is intended to safeguard national interests amid shifting domestic and international dynamics. The article also evaluates the relevance and applicability of Bhandari's vision in the context of current global changes. A descriptive-analytical approach is employed, drawing on both primary and secondary sources. The analysis is informed by constructivism and role theory, which help interpret the normative foundations and practical roles envisioned by PMPD for Nepal in the international sphere. The findings suggest that while Foreign Policy 2020 incorporates many elements of PMPD’s vision, significant gaps remain in its implementation and contextual adaptation. By examining the alignment between political ideology and foreign policy practice, this study contributes to a deeper understanding of how historical political visions can influence contemporary foreign policy in Nepal.